Burglar alarm / Ahmad Azrin Mohd. Naseer - Mohd. Naseer, Ahmad Azrin (2002)
Burglar alarm is an apparatus, which is used to give warning through the sound o f bell or noises. This gadget is used to protect the owner’s property from being broken into or stolen. In project, the alarm is hanging at doorknob, in more details we use a bare wire as a sensor and put at Door Knob when someone touch the Door Knob the sensor will detect and activate and activate the siren. The siren will give a beeping sound as a warning to owners. To stop the alarm we use a remote control to stop the beeping sound and activate the circuit back. It is more easily to owners using a remote control rather than switch. This Alarm will not effect to people who touch the Door Knob because there is no current at the Door Knob but this circuit is use for detect a touch only.